Transforming Grief into Eternity: A Riffaterrian Semiotic Analysis of the Poem "Al-ān ṣurta jamīʿanā" by Muhammad Al-Turki - -, Hesti Dwi Ira Utami ((الطموحات ) EL-THUMUHAT, 2026)
Abstract This study reveals the strategy of constructing the meaning of eternity in the poem “Al-ān ṣurta jamīʿanā” by Muhammad Al-Turki as a response to the death of the legendary Saudi Arabian poet, Badr bin Abdul Mohsen, on May 4, 2024. Using Michael Riffaterre's semiotic approach with a qualitative-descriptive method, the analysis was conducted in four stages: discontinuity of expression, heuristic reading, hermeneutic reading, and identification of matrices, models, and hypograms. The findings show the use of personification, metaphor, and paradox that transform the narrative of personal loss into an eternal collective identity. The matrix of “transforming loss into eternity” is actualized in the model “now you have become all of us.” The hypogram analysis reveals the roots of classical Arabic ritsa tradition and modern free verse poetry that refer to Badr as a national cultural icon. This research confirms Al-Turki's success in transforming mourning into a tribute to eternal cultural values, while also demonstrating social media as a space for the actualization of ritsa tradition in the digital age. Keywords: Riffaterre’s Semiotics, Modern Arabic Poetry, Badr bin Abdul Mohsen.